Investigative Attitudes in Students of the Academic Unit of General Studies (Docentes 2.0 Journal, 2025)
Attitudes related to scientific study are fundamental aspects of professional training; they allow the generation of knowledge and the resolution of problems. The research objective was to determine the differences in the research attitudes of students of the Academic Unit of General Studies of a Peruvian university according to the academic cycle. The inquiry was based on the hypothetical-deductive method and positivist paradigm, with a quantitative approach, non-experimental design, descriptive-comparative type, and cross-sectional. The sample consisted of 269 participants from the first cycle and 182 from the fourth cycle. The Scale of Attitudes Towards Research (EACIN) survey technique was applied and validated with a Cronbach alpha coefficient of 0.85. The results showed an indifferent attitude in 74% of those in the first cycle, decreasing to 62.1% in the fourth cycle. On the other hand, the favorable attitude increases from 17.1% to 34.1% in the same period. The data indicate significant differences between progress in the academic period and an increase in interest, possibly explained by more frequent exposure to analysis and academic exploration activities. Unlike previous research, the results underline the need for universities to adopt approaches incorporating academic analysis in the study programs, promoting continued interest in this area among participants.
Keywords: Research attitudes; university student; general studies; research skills